The Effect of Organizational Climate on Employee Job Satisfaction with Work Ethics as A Moderating Variable - Jufrizen Jufrizen; Sandra Pratiwi (AIBPM Publisher, 2021)
The purpose of this study was to determine and analyze the effect of Organizational Climate on Employee Job Satisfaction with Work Ethics as a moderating variable of the study at PT Indonesia Asahan Aluminum either directly or indirectly. The approach used in this study is an associative approach. The population in this study were 2.057 employees of PT Indonesia Asahan Aluminum while the sample in this study were 30 employees of PT Indonesia Asahan Aluminum. Data collection techniques in this study used interview techniques, documentation studies, observation, and questionnaires. The data analysis technique in this study used the partial least square – structural question model (PLSSEM), Hypothesis Testing (t test and F test), and the coefficient of determination. The results of this study prove that the organizational climate is directly significant to employee job satisfaction and directly work ethics does not moderate the effect of organizational climate on employee job satisfaction at PT Indonesia Asahan Aluminum.